Analysis Of Islamic Education Policy in The National Education System Law No. 20 Year 2003 - John Eka Powa; Minnah El Widdah; Hamdi Zas Pendi (Journal of Curriculum and Pedagogic Studies (JCPS), 2023)
This study aims to analyze the Islamic education policy in the National Education System Law No. 20 of 2003. This law is a historical milestone for Islamic education in Indonesia as it provides clear legal recognition and legitimacy for Islamic religious education. The study discusses the content of the National Education System Law No. 20 of 2003 related to Islamic education, as well as the analysis of policies and strategies used to develop Islamic education in Indonesia. This research uses a literature review methodology, involving the search, selection, and evaluation of sources related to Islamic education policy in Indonesia, particularly in the National Education System Law No. 20 of 2003. In its analysis, the study shows that the National Education System Law No. 20 of 2003 provides sufficient space for the development of Islamic education, but greater and more integrated efforts are still needed between the government, society, and Islamic educational institutions to optimize the implementation of these policies. This research can serve as a reference for policy makers and Islamic education practitioners in developing Islamic education in Indonesia.